Pedro Penduko, Filipino Comic Superhero: comparative studies between comic and screen adaptation - Josephine May Grace Aclan Famoso (Universitas Ahmad Dahlan, 2021)
This study intended to compare Filipino komiks from its film adaptation. In particular, it explores the form and content in Pedro Penduko (1954) and the film adaptation, Pedro Penduko, Episode II: The Return of the Comeback (2000) using the Formalistic Approach in literary criticism. The study highlights the elements such as characters, symbols, and themes. In brief, the characters in the komiks exemplify Filipino identity. However, the film version provides comic relief. Looking at symbols, the komiks used an amulet common to Filipino culture. The film, on the other hand, showcases a magical promotional vehicle. The theme in the komiks is concerned with issues as noteworthy as identity and culture, while the film spectacles self-interest. It was discovered that the komiks form contributes to a great sense of Filipino art. However, its film adaptation lacks the same qualities. The demand for significant visual outputs come from an audience who hope to see visual arts that are not just profitable works of art but are socially relevant and geared towards the promotion of nationalism